EFEKTIVITAS ARANG AKTIF KAYU DENGAN VARIASI UKURAN ADSORBEN DAN DEBIT ALIRAN DALAM MENURUNKAN KADAR KADMIUM (Cd) PADA LIMBAH CAIR PERTANIAN - Ida Rofida; Nur Endah Wahyuningsih; Nurjazuli Nurjazuli (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The use of fertilizer and pesticides that can not be controlled continuously in agricultural activities had impacts on environmental pollution and human health. Based on preliminary studies, cadmium level in the agricultural area in the Brebes area was 0.028 mg/l which exceeded from the existing quality standard of 0.01 mg/l. The aim of this study was to determine the effectiveness of activated charcoal made from Accacia mangium wood with various sizes of adsorbents and flow discharge to reduce cadmium levels in fertilizer solution. The type of this research was true experimental with pretest-posttest design with control group. The sample that was used in this reseach was TSP fertilizer solution. The variations of adsorbent size were gravel (4 mesh), granule (8 mesh), and powder (100 mesh) while variations of discharge flow were 100 ml / minute, 75 ml/minute, and 50 ml/minute. Kruskal-Wallis Test with 95% confidence level indicated that there were significant differences between treatments. The results showed that the size of the adsorbent powder (100 mesh) and discharge flow of 50 ml / min was the treatment with the highest decrease in the average cadmium level of 0,192 mg/L (49.87%). Therefore, activated wood charcoal was quite effective in reducing cadmium levels but still above TLV (Threshold Limit Value) standard.